IMPLEMENTATION OF GRAPH COLORING USING THE WELCH POWELL ALGORITHM IN SCHEDULING THESIS PROPOSAL SEMINARS IN THE MATHEMATICS STUDY PROGRAM AT UNIVERSITAS NEGERI MEDAN - Nurul Maulida Surbakti (Deli Sains Informatika, 2023)
The process of arranging thesis proposal seminar schedules in the Department of Mathematics, Universitas Negeri Medan often encounters difficulties due to the large number of students who will hold seminars at the same time. So far, the scheduling process has been done manually, resulting in the schedule of thesis supervisors and examiners often conflicting with the schedules of other student seminars. To overcome this problem, the schedule is arranged by applying the concept of vertex coloring on a graph using the Welch Powell Algorithm. In the graph, vertices represent students who will hold seminars, while edges connecting two vertices indicate that the two students have one or two common thesis supervisors. This study uses a literature review method and the results show that graph coloring with the Welch Powell Algorithm can be used to arrange schedules for thesis proposal seminars in the Department of Mathematics, Faculty of Mathematics and Natural Sciences, Universitas Negeri Medan.